Overcoming the challenges of Funding Sustainable Entrepreneurship in Africa - Derdabi, Ayoub; Dvouletý, Ondřej; Blažková, Ivana; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
Sustainable entrepreneurship is essential to tackle the negative effects of climate change especially in the African context where the damages have been extensive. Despite the urgency, sustainable entrepreneurs often face substantial barriers in creating value, securing necessary funding, and achieving scalability especially in African countries. This study is an exploration of the landscape of funding for sustainable entrepreneurship in Africa to understand how entrepreneurs get access to funds to develop and grow their businesses. The review of the literature reveals that although the body of literature on this field is still in its early stages, there has been a notable increase in scholarly interest over the past five years. This research adopts an empirical qualitative methodology that analyzes the existing literature in the field of sustainable entrepreneurship funding through a systematic literature review and a bibliometric analysis. The research delves into the context of sustainable entrepreneurship funding in Africa through a phenomenological research and case studies. This thesis aims to participate in the research field of sustainable entrepreneurship by offering insights on the general context of sustainable entrepreneurship funding and into the specific characteristics of funding sustainable ventures in the continent. It explores the range of available funding mechanisms, identifies the main challenges faced by sustainable entrepreneurs, and the strategies employed to tackle them. The insights gained from this research are intended to both scholars and practitioners including African entrepreneurs, investors, supporting ecosystems and policy makers. It can ultimately contribute to the development of more effective funding strategies and policies for the development of sustainable entrepreneurship in Africa.
Vedoucí práce: Ondřej Dvouletý
Závěrečná práce - Institut celoživotního vzdělávání (DBA)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet